Concise review: Current understanding of extracellular vesicles to treat neuropathic pain - Zhang, Kexin; Li, Pei; Jia, Yuanyuan; Liu, Ming; Jiang, Jingjing (Frontiers in Aging Neuroscience, 2023)
Extracellular vesicles (EVs) including exosomes are vesicular vesicles with phospholipid bilayer implicated in many cellular interactions and have the ability to transfer multiple types of cargo to cells. It has been found that EVs can package various molecules including proteins and nucleic acids (DNA, mRNA, and noncoding RNA). The discovery of EVs as carriers of proteins and various forms of RNA, such as microRNAs (miRNA) and long noncoding RNAs (lncRNA), has raised great interest in the field of drug delivery. Despite the underlying mechanisms of neuropathic pain being unclear, it has been shown that uncontrolled glial cell activation and the neuroinflammation response to noxious stimulation are important in the emergence and maintenance of neuropathic pain. Many studies have demonstrated a role for noncoding RNAs in the pathogenesis of neuropathic pain and EVs may offer possibilities as carriers of noncoding RNAs for potential in neuropathic pain treatment. In this article, the origins and clinical application of EVs and the mechanism of neuropathic pain development are briefly introduced. Furthermore, we demonstrate the therapeutic roles of EVs in neuropathic pain and that this involve vesicular regulation of glial cell activation and neuroinflammation.